Template matching-based mobile learning application for effective lampung script writing practice - Nurcahyo, Widyat; Fatoni, Ahmad; Faizah, Novianti M. (Jurnal Mandiri IT, 2025)
Preserving the traditional Lampung script is crucial for maintaining local cultural identity amid globalization. This study develops an interactive mobile learning application to engage students in studying the Lampung script. The application aids in learning characters and writing methods through features like pronunciation audio, practice questions, and writing exercises. Using the template matching method, the writing exercise feature provides accurate feedback, helping students identify and correct mistakes. Research involved eighth-grade junior high students and local language teachers as informants. Application testing utilized Blackbox Testing to evaluate functionality and template matching accuracy, yielding satisfactory results in handwriting recognition. User feedback indicated positive reception: 95% of students found the application interactive, 90% deemed it interesting, and 100% reported it supported their learning of the Lampung script. Furthermore, 98% expressed interest in using the application in school activities. This mobile application effectively enhances student interest and motivation to learn the traditional Lampung script, contributing to the preservation of local culture through education.